Weight loss and changes in adipose tissue and skeletal muscle volume after laparoscopic sleeve gastrectomy and and Roux-en-Y gastric bypass: a prospective study with 12-month follow-up - Kenngott, Hannes Götz; Nickel, Felix; Wise, Philipp Anthony; Wagner, Felix; Billeter, Adrian; Nattenmüller, Johanna; Nabers, Diana; Maier-Hein, Klaus H.; Kauczor, Hans-Ulrich; Fischer, Lars; Müller, Beat P. (Obesity surgery, 2019)
This study aimed to evaluate changes in body tissue composition with obesity surgery regarding visceral fat, subcutaneous fat, and skeletal muscle.
Gesehen am 15.04.2020